Instrumentação e análise térmica do processo de produção de carvão vegetal - Oliveira, Rogério Lima Mota de (2009)
The quality of charcoal production produced by a kiln is strongly dependent on the procedures of temperature control inside of the kiln. However, in practical applications, there are no thermal models and the temperature control is usually done by a carbonizing agent from visual verifications of the coal smoke. In addition, green wood time of drying, forecast production time and carbonization homogeneity are also variables to be controlled by the carbonizing agent. It means, this quality control is dependent the agent experience and is very inefficient. The main objective of this work is to use temperature measurement from thermocouple located in various points inside the kiln to establish a relationship between temperature and quality charcoal. In this sense, a control automatic procedure can, then, be developed. Due to the characteristic of the aggressive combustion medium, temperature data acquired from the thermocouples will be sent to be processed by a wireless net system. This measurement procedure with a statistical analysis represents an important tool to reduce the time of drying, pyrolysis and cooling. This procedure can also minimize the losses and increase the thermal efficiency considering the charcoal historical production of the plant analyzed. Another important consequence of this work is the contribution to reduce greenhouse effect gas emission.